PENGARUH PERSON ORGANIZATION FIT (P-O FIT) DAN KEPRIBADIAN TERHADAP KINERJA PEGAWAI DENGAN MEDIASI KOMITMEN ORGANISASIONAL (Studi Terhadap Pengelola Manajemen Informasi Kesehatan Dinas Kesehatan Kota Semarang) - Suhito, Hanif Pandu; Rozak, Hasan Abdul (Jurnal Ilmiah Telaah Manajemen, 2017)
The main goals of this research is to analyze the impact of person-organization fit (P-O Fit), personality, on employee performance using organizational commitment as mediator (study at Health Information Management Division on Distict Health Office of Semarang City). The problem that exist was associated with lower of employee performance. The population in this research is all of the officer related health information management in Distict Health Office of Semarang City as many as 275 officers and 123 officer as sample. Methode of data collection is observation, documentation, dan questionnaire. Analysis methode use instument test (validity and reliability testing), percentage of descriptive analysis, regression analysis, model test, and hypothesis test. The result of this research are: (1) P-O Fit has significant and positive influence on organizational commitment, (2) Personality has significant and positive influence on organizational commitment, (3) P-O Fit has significant and positive influence on employee performance, (4) Personality has significant and positive influence on employee performance, (5) Organizational commitment has significant and positive influence on employee performance, and has mediated P-O Fit and personality influence on employee performance, but the influence of P-O Fit and personality on employee performance, more effective directly than through organizational commitment. Keywords: Person Organizational Fit (P-O Fit), Personality, Organizational Commitment, Employee Performance.